Something Blue - Giffin, Emily (New York St. Martin's Press, 2011)
Giffin's sophomore effort-which tells the story that her bestselling Something Borrowed did from a different character's point of view-stars such an unsympathetic narrator that it's a little like reading a Cinderella story featuring one of the wicked stepsisters. Perhaps beautiful Darcy Rhone isn't really wicked, but she is one of the most shallow, materialistic, self-centered and naïve 29-year-olds around. Ostensibly a high-powered PR person in Manhattan (though she never seems to work), Darcy spends most of her time shopping, partying and getting ready for her wedding to perfect guy Dex. But an alcohol-fueled Hamptons fling with one of Dex's pals, Marcus, starts to break Darcy's perfect life down; and discovering Dex hiding in her best friend Rachel's closet really shatters it. Pregnant with Marcus's baby, Darcy decamps for London, where she crashes in high school pal Ethan's flat and annoys the heck out of him with her endless shopping and complete disregard for her impending motherhood. But after a good lecture from Ethan, whom Darcy has started to fall for a little, Darcy embarks on a self-improvement plan, thereby demonstrating she can think about someone besides herself. And if readers don't mind the first 200 pages in which she doesn't, they'll enjoy her happy ending and the few surprises along the way. Fans of Something Borrowed, too, may relish the "she said, she said" fun.
Keywords: Pregnant women